Report on the Observance of Standards and Codes on Accounting and Auditing : Albania Update - World Bank (World Bank, Vienna, 2020)
Albania's remarkable economic transformation has been affected by the global financial crisis. The country's main challenges include maintaining macro-fiscal and financial sector sustainability, improving the investment climate and unleashing private sector growth, removing barriers to employment for job creation, and improving governance and public service delivery. Improving the business climate and addressing gaps in infrastructure and labor force skills are necessary to reap the early benefits of European Union (EU) accession and make Albania attractive for foreign direct investments. This report on the observance of standards and codes in accounting and auditing (ROSCA and A) seeks to assist with the further development of the financial reporting institutional framework in Albania. The report summarizes key findings, identifies gaps, and makes recommendations for consideration by the authorities to improve alignment with international standards and good practice.